Pattern of the impact of social capital on crisis management performance - khadije khatiri; iran ghazi; nemat hasani (تحقیقات کاربردی علوم جغرافیایی)
Natural disasters cause severe financial and human damage. Crisis management means purposefully shifting the flow of affairs in a controllable manner with the intention of returning things to pre-crisis conditions as soon as possible. Therefore, the main purpose of this article is to present a model of social capital development in urban water crisis management.The study method is descriptive-survey. In order to collect information, interviews and questionnaires were used and for data analysis, SPSS software, AHP analysis method, regression and T were used. Statistical community including crisis and water crisis managers; Also, all residents of Karaj were in the period between 1396 and 1395, which was estimated as a statistical sample of 350 people using Cochran's table.The results of statistical analysis showed that from the perspective of statistical sample individuals, the amount of social capital was lower than the desired level. Also, the relationship between social capital indicators was significant. Also, the results of couple comparison of main criteria using AHP analysis prioritized the indicators of social trust with 0.433 coefficient, incentive policy criterion and change in attitude space with 0.355 coefficient, criterion The interactive and value infrastructure of the society with a coefficient of 0.277, the interaction with a coefficient of 0.203, and finally the criterion of non-alienation with the government with a coefficient of 0.199 showed the fifth priority.The study shows that countries' ability to deal with crises has a lot to do with crisis management policy, promoting social capital in society and developing a spirit of cooperation and motivating participation among the people is one of the important solutions.